Paradise by the far-red light: Far-red and red:blue ratios independently affect yield, pigments, and carbohydrate production in lettuce, Lactuca sativa - Van Brenk, Jordan B.; Courbier, Sarah; Kleijweg, Celestin L.; Verdonk, Julian C.; Marcelis, Leo F. M. (Frontiers in Plant Science, 2024)
In controlled environment agriculture, customized light treatments using light-emitting diodes are crucial to improving crop yield and quality. Red (R; 600-700 nm) and blue light (B; 400-500 nm) are two major parts of photosynthetically active radiation (PAR), often preferred in crop production. Far-red radiation (FR; 700-800 nm), although not part of PAR, can also affect photosynthesis and can have profound effects on a range of morphological and physiological processes. However, interactions between different red and blue light ratios (R:B) and FR on promoting yield and nutritionally relevant compounds in crops remain unknown. Here, lettuce was grown at 200 µmol m-2 s-1 PAR under three different R:B ratios: R:B87.5:12.5 (12.5% blue), R:B75:25 (25% blue), and R:B60:40 (40% blue) without FR. Each treatment was also performed with supplementary FR (50 µmol m 2 s 1; R:B87.5:12.5+FR, R:B75:25+FR, and R:B60:40+FR). White light with and without FR (W and W+FR) were used as control treatments comprising of 72.5% red, 19% green, and 8.5% blue light. Increasing the R:B ratio from R:B87.5:12.5 to R:B60:40, there was a decrease in fresh weight (20%) and carbohydrate concentration (48% reduction in both sugars and starch), whereas pigment concentrations (anthocyanins, chlorophyll, and carotenoids), phenolic compounds, and various minerals all increased. These results contrasted the effects of FR supplementation in the growth spectra; when supplementing FR to different R:B backgrounds, we found a significant increase in plant fresh weight, dry weight, total soluble sugars, and starch. Additionally, FR decreased concentrations of anthocyanins, phenolic compounds, and various minerals. Although blue light and FR effects appear to directly contrast, blue and FR light did not have interactive effects together when considering plant growth, morphology, and nutritional content. Therefore, the individual benefits of increased blue light fraction and supplementary FR radiation can be combined and used cooperatively to produce crops of desired quality: adding FR increases growth and carbohydrate concentration while increasing the blue fraction increases nutritional value.